(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
The purpose of this study was to measure temperatures of cotton and polyester woven fabrics in wetting and drying process by thermocouples placed on them. It also discussed temperature distribution caused by diffusion and evaporation at different relative humidity. The measurement points of thermocouples were located at two concentric circles with radius of 3 cm and 6 cm. The temperatures were measured by covering the same fabric when a droplet of water dropped on the center of circle at 20%RH, 65%RH and 80%RH environmental moistures, respectively. The results showed that because of diffusion determined by distance, it was different of temperature changes of every point. As the center of circle, at different humidity, temperatures when reached dynamic heat balance were different. The drying process of cotton showed consistency with temperature recovery. At 20%RH, it is the shortest for temperature returning to environmental temperature because of diffusion speed caused by steam content of environment. It can be applied to performance assessment for fabrics that liquid water absorbing function is required. It also can be used for evaluation of discomfort of wet fabrics by temperature decline with the wetting.